The role of tumour necrosis factor in hepatitis B infection: Jekyll and Hyde. Issue 12 (9th December 2016) - Valaydon, Zina; Pellegrini, Marc; Thompson, Alexander; Desmond, Paul; Revill, Peter; Ebert, Gregor
Abstract : Chronic hepatitis B (CHB) is a major health problem worldwide and is associated with significant long‐term morbidity and mortality. The hepatitis B virus (HBV) is a hepatotropic virus that is capable of integrating in the host nucleus permanently resulting in lifelong infection. To date, there is no definitive cure for HBV, as our current treatments cannot eradicate the viral reservoir that has integrated in the liver. Elucidating the immunopathogenesis is key to finding a therapeutic target for HBV as the virus is not in itself cytopathic but the immune response to the virus causes the majority of the cellular injury. In most cases, the virus reaches a state of equilibrium with low viral replication constrained by host immunity. Multiple cytokines have been implicated in the pathogenesis of CHB. Tumor necrosis factor (TNF) has emerged as a key player; on one hand it can facilitate immune‐mediated virological control but on the other hand it can cause collateral hepatocyte damage, cirrhosis and possibly promote hepatocellular carcinoma. In this review, we discuss the current understanding of the immunopathogenesis of HBV, focusing on TNF and whether it can be harnessed in therapeutic strategies to cure HBV infection.